Peak load relief in MV/LV distribution networks through smart grid-enabled CVR with droop control EV2G reactive power support - Singh S.; Singh S.P. (My University, 2025)
Investigation on combined impact of smart grid enabled conservation of voltage reduction (CVR) and electric vehicle (EV) to grid (EV2G) reactive power (Q) support has been presented in this paper. CVR is deployed through advance volt-VAr control (VVC) method. In order to assess the combined effect CVR and EV, the VVC operation has been carried out in three different modes such as No-CVR, only CVR and CVR with EV reactive power support. In order to determine the desired reactive power support, a droop controlled scheme has been applied for EV charging station. The impact of CVR and EV is demonstrated on modified IEEE 13 node test feeder of the radial distribution network with voltage dependent load model. Modeling and simulations have been done in open distribution system simulator (OpenDSS) interfaced with MATLAB environment. The simulation result reveals that the significant amount of peak load demand reduction has been achieved with the only CVR operation. However, during the deeper level of voltage reduction through only CVR mode, the violation of minimum node voltage limit and higher system losses are observed. Therefore, the coordinated operation of CVR and EV is very helpful in order to maintain the feeder voltage profile within the limits and reduce the system losses, even in the deeper level of voltage reduction. Moreover, the simulation results also demonstrate that the CVR with EV mode yields better results in terms of higher peak power shaving, improvement in voltage profile and reduction in losses in comparison to only CVR. © 2018 IEEE.